Determinação da capacidade de troca de cátions, do solo por fotometria de chama - Glória, N. A. da; Catani, R. A.; Matuo, T. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1965)
This paper describes a method for determining cation exchange capacity of soils (C.E.C.).Two grams sample of 9 different soils were placed in a percolation tube with diammeter of 15 mm and lenght of 200 mm. Twenty mililiters of normal calcium acetate solution pH = 7,0 were percolated through the soil. Excess of calcium acetate was washed with ethyl alcohol 80% (80 parts of alcohol plus 20 parts of water, in volume) by suction. Adsorbed calcium was extratecd with 50 ml of normal ammonium acetate solution (pH - 7,0) by suction. Calcium extratecd by ammonium acetate solution was determined by photometry.The method described is very rapid and afford a good precision, according to table 1.